Histone H3E73Q and H4E53A mutations cause recombinogenic DNA damage - Pedro Ortega; Desiré García-Pichardo; Marta San Martin-Alonso; Ana G. Rondón; Belén Gómez-González; Andrés Aguilera (Microbial Cell)
The stability and function of eukaryotic genomes is closely linked to histones and to chromatin structure. The state of the chromatin not only affects the probability of DNA to undergo damage but also DNA repair. DNA damage can result in genetic alterations and subsequent development of cancer and other genetic diseases. Here, we identified two mutations in conserved residues of histone H3 and histone H4 (H3E73Q and H4E53A) that increase recombinogenic DNA damage. Our results suggest that the accumulation of DNA damage in these histone mutants is largely independent on transcription and might arise as a consequence of problems occurring during DNA replication. This study uncovers the relevance of H3E73 and H4E53 residues in the protection of genome integrity.